Improving Bhinneka Tunggal Ika Learning Outcomes Through Team Games Tournament in Fourth Grade at State Elementary School 03 Binuang - Rafianda, Zhafirah; Desyandri , Desyandri (Journal of Basic Education Research, 2026)
Purpose of the study: This study aims to improve students’ learning outcomes in Bhinneka Tunggal Ika learning by implementing the Team Games Tournament (TGT) learning model in Grade IV of SDN 03 Binuang Kampung Dalam Methodology: This research employed Classroom Action Research with qualitative and quantitative approaches. The research was conducted in two cycles consisting of planning, action, observation, and reflection. The subjects were 20 fourth-grade students. Data were collected through tests and non-test techniques such as observation sheets for lesson plans, teacher activities, student activities, and learning outcomes. Data were analyzed using descriptive qualitative and quantitative analysis. Main Findings: The results showed an improvement in learning outcomes from Cycle I to Cycle II. Lesson plan quality increased from 92.96% to 98.43%. Teacher activity improved from 85.71% to 96.42%, and student activity increased from 82.14% to 96.42%. Students’ learning outcomes also improved in attitude (77.65 to 86.25), knowledge (75.25 to 87), and skills (80.40 to 89.99). Novelty/Originality of this study: This study integrates the TGT model into Bhinneka Tunggal Ika learning in elementary education, emphasizing collaborative games to enhance attitudes, knowledge, and skills simultaneously, which strengthens student engagement and learning effectiveness.